Bulgaria : 2006 Article IV Consultation, Third Review Under the Stand-By Arrangement, and Request for Rephasing, Waiver of Applicability and Nonobservance of Performance Criteria and Extension of the Arrangement-Staff Report; Staff Statement; and Public Information Notice and Press Release on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2006)
The current account deficit in Bulgaria, which doubled in 2005 to 11.8 percent of GDP, deteriorated further to 14.6 percent of GDP during the first four months of 2006. The current account deficit continues to be substantially financed by foreign direct investment (FDI) flows. Fiscal policy has been cautious for several years, and is being tightened further in 2006. The Bulgarian National Bank (BNB) introduced successively tighter credit limits and enhanced prudential measures. The discussions centered on policies to contain macroeconomic imbalances and achieve sustainable high growth.